2021
DOI: 10.1177/17531934211000579
|View full text |Cite
|
Sign up to set email alerts
|

Minimal incision bone graft and screw fixation for scaphoid nonunion with substantial bone loss

Abstract: Informed consent Informed consent for non-identifiable patient information and images to be published was provided by the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Ahrend et al . 15 studied the distribution of scaphoid volumetric bone mineral density (VBMD), and found that the peripheral region had high VBMD, while the center and waist had the lowest VBMD, which explained why most common fractures appeared in the waist. Apart from this, the small volume of the scaphoid and the abundant ligaments of the peripheral joints have also brought great treatment challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahrend et al . 15 studied the distribution of scaphoid volumetric bone mineral density (VBMD), and found that the peripheral region had high VBMD, while the center and waist had the lowest VBMD, which explained why most common fractures appeared in the waist. Apart from this, the small volume of the scaphoid and the abundant ligaments of the peripheral joints have also brought great treatment challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The blood supply of the scaphoid mainly comes from the nourishing vessels of the scaphoid waist, which also explained why it is easy to develop aseptic necrosis and fracture nonunion after scaphoid lumbar fracture. Ahrend et al 15 studied the distribution of scaphoid volumetric bone mineral density (VBMD), and found that the peripheral region had high VBMD, while the center and waist had the lowest VBMD, which explained why most common fractures appeared in the waist. Apart from this, the small volume of the scaphoid and the abundant ligaments of the peripheral joints have also brought great treatment challenges.…”
Section: Main Findings Of the Studymentioning
confidence: 99%